Nailfold Capillaroscopy With USB Digital Microscopy in Connective Tissue Diseases: A Comparative Study of 245 Patients and Healthy Controls - Chanprapaph, Kumutnart; Fakprapai, Wuttidej; Limtong, Preeyachat; Suchonwanit, Poonkiat (Frontiers in Medicine, 2021)
Background: Nailfold capillaroscopy (NFC) is a valuable tool to detect microcirculation abnormalities in connective tissue diseases (CTDs). However, whether the universal serial bus (USB) digital microscopy used as onychoscopy is as effective as the videocapillaroscopy in determining the diagnostic and prognostic values of CTDs remains to be determined. Objective: To investigate NFC features of systemic lupus erythematosus (SLE), dermatomyositis (DM), and systemic sclerosis (SSc) patients and compare with normal controls as well as examine which feature could differentiate among CTDs. Furthermore, we aim to explore different capillaroscopic abnormalities and their association with disease activity. Methods: Nailfold images were taken from patients and healthy controls using a USB digital microscopy. Patterns on the capillary morphology, diameter, architecture, and density were recorded and compared. We further determined the NFC findings in SLE, DM, and SSc and corresponded to their respective disease activity scoring system. Results: A total of 245 participants, consisting of 54 SLE, 32 DM, and 51 SSc patients, as well as 108 controls, were enrolled. All capillaroscopic features, except for tortuous capillaries, were significantly more common in CTDs than healthy control (all P<0.05). A multinomial logistic regression analysis revealed that bushy capillaries had significantly higher odds for both SLE and DM than SSc (OR 4.10, 95%CI 1.71-9.81, P=0.002 and OR 7.82, 95%CI 2.86-21.38, P<0.001, respectively). Elongated capillaries demonstrated significant odds for SLE compared to SSc (OR 3.35, 95%CI 1.005-11.20, P=0.049), while prominent subpapillary plexus showed greater odds for SLE compared to both DM and SSc (OR 2.75, 95%CI 1.07-7.02, P=0.03 and OR 5.78, 95%CI 2.29-14.58, P<0.001, respectively). The presence of hemorrhage, enlarged capillaries, and the low-density index had significantly higher odds in favor of SSc than SLE. Bushy capillaries were the only pattern with a strong association for DM over SSc. The presence of enlarged capillaries indicated higher SLE severity, but no specific finding was related to DM or SSc skin scores. Conclusions: Nailfold capillaroscopic examination using a digital microscope is a valuable method for the diagnosis of SLE, DM, and SSc. Several morphologic patterns can help differentiate among CTDs; however, the prognostic significance of this method requires further investigations.